เพลงร้องยุคคลาสสิก - สุนทรธนผล นัฏฐิกา; วิบูลย์ภาณุเวช วิภาต (Fine Arts Journal: Srinakharinwirot University, 2018)
The purpose of this article is: (1) To collect and categorize music of the classical music including: Masses, Oratories, and Opera (2) To explore the characteristics of classical period compositions. (3) To define for the characteristic style of classical period composers. Music of the classical period is Absolute music. Vocal music of the classical period was losing popularity because audiences preferred the opera which was becoming more fashionable at that time. Nevertheless, single compositions were still being composed. Classical music differentiated itself from Baroque music by its use of homophony. The piano ensemble make the main melody improvable. Religious compositions were still popular at the time. There are many famous Masses for instance: Franz Joseph Haydn, Wolfgang Amadeus Mozart, and Ludwig van Beethoven.